ANALISIS HUKUM PENOLAKAN WARGA REMPANG TERHADAP RELOKASI PEMUKIMAN PERUNTUKAN PEMBANGUNAN PROYEK STRATEGIS NASIONAL REMPANG ECO CITY - STEVEN JINGGA (ALWAQFU: Jurnal Hukum Ekonomi dan Wakaf, 2024)
Exciting news came from Batam, precisely on September 7 and 11 2023, a series of clashes between Rempang community members and police officers due to community members' rejection of the Rempang Eco City National Strategic Project (PSN) which was to be implemented in Batam. The conflict that occurred between residents of the Rempang community and the police occurred as a result of the government's policy of relocating residential areas where residents of the Rempang community lived, with orders to immediately move from the area where they lived. This sudden order clearly caused the residents of Rempang to panic and become angry with the Government. Because they didn't know and were given news beforehand that the area where they lived would be the object of PSN Rempang Eco City. And if the residents are relocated, they will be confused about their future, because the majority of Rempang residents work as fishermen and farmers. The type of research is a normative juridical approach in this research and uses qualitative analysis techniques which are then explained and analyzed using analytical descriptive methods. The type of approach used in writing this thesis is a library research approach, namely by studying books and documents related to the topic of the article and also using a statutory regulatory approach, namely by reviewing existing statutory regulations. related to the topic discussed in this research The results of the research and discussion in this research showed that the residents of the Rempang community were disappointed with the government's policy which they felt was urgent, the government's methods were considered inappropriate and wise and ignored the local wisdom of the Rempang residents themselves. Because there was no previous discussion with Rempang residents about the Rempang Eco City PSN plan which would be implemented using their territory. Where in this area, the residents of the community have been regenerating for generations, occupying the area as a village where they live. Finally, the Rempang residents fought back and demanded that the government resolve this problem properly.